(untitled) (College of Basic Education Research Journal, 2025)
Technical development in last decade started relatively slow and then turned into a cognitive and cultural explosion that is often uncontrollable. As literary and critical studies are not isolated from this great development, Arab critics have kept pace with it with writings in response to this change, but this response may be a double-edged sword; the first is a collision and direct confrontation with this development, while the second is going with flow in a way that matches technical developments that are taking place in a way that may be understood as a promotion of this technical development. Destruction meant in this research is a cultural one that may be storming Arab culture out of nowhere; Twitter culture from the point of view of (Dr. Abdullah al-Ghadami) may be a real destruction of old Arab cultural centralization; or concept of (cultural blindness) in one of its aspects is a question about (hegemony) whether it is an extension of legitimization of minority and its submission to central culture? Therefore, this research will stop at books that I believe provide us with answers to questions, most notably: - Is cultural destruction a dismantling of traditional values? - Is individual voice versus collective is a form of cultural destruction? - Is cultural hegemony a cultural destruction or power domination? - Is digital heroism and group tweets a cultural destruction or a response to changes of times? These and other questions will be answered through a comprehensive critical examination that follows strategies of critique of a range of critical studies, namely: - Twitter Culture - Freedom of Expression or Responsibility of Expression Abdullah Al-Ghadhami (2016). - I am an Islamist, so I exist - Transformations of ego in virtual age Said Benkrad (2016). - Cultural blindness from hegemony of institution to legitimization of minority Hani Al-Younis (2019). بدأ التطور التقني في العقد الماضي بطيئًا نسبيًا ثم تحول إلى انفجار معرفي وثقافي غالبًا ما لا يمكن السيطرة عليه. ولم تكن الدراسات الأدبية والنقدية بمعزل عن هذا التطور الكبير، فقد واكبه النقاد العرب بكتابات ردا على هذا التغيير، لكن هذا الرد قد يكون سلاحا ذا حدين؛ الأول هو الاصطدام والمواجهة المباشرة مع هذا التطور، والثاني هو السير بشكل ينسجم مع التطورات التقنية التي تحدث بشكل يمكن فهمه على أنه تعزيز لهذا التطور التقني. التدمير المقصود في هذا البحث هو تدمير ثقافي قد يقتحم الثقافة العربية من العدم؛ ثقافة تويتر من وجهة نظر (د.عبدالله الغدمي) قد تكون تدميراً حقيقياً للمركزية الثقافية العربية القديمة؛ أم أن مفهوم (العمى الثقافي) في أحد جوانبه هو السؤال عن (الهيمنة) هل هي امتداد لشرعنة الأقلية وخضوعها للثقافة المركزية؟ ولذلك سيتوقف هذا البحث عند الكتب التي أعتقد أنها تقدم لنا أجوبة عن تساؤلات أبرزها: - هل التدمير الثقافي هو تفكيك للقيم التقليدية؟ - هل الصوت الفردي مقابل الصوت الجماعي هو شكل من أشكال التدمير الثقافي؟ - هل الهيمنة الثقافية تدمير ثقافي أم هيمنة على السلطة؟ - هل البطولة الرقمية والتغريدات الجماعية تدمير ثقافي أم استجابة لتغيرات الزمن؟ هذه الأسئلة وغيرها سيتم الإجابة عليها من خلال فحص نقدي شامل يتبع استراتيجيات نقد مجموعة من الدراسات النقدية، وهي: - ثقافة تويتر – حرية التعبير أم مسؤولية التعبير / عبدالله الغدامي (2016). - أنا إسلامي إذن أنا موجود - تحولات الأنا في العصر الافتراضي / سعيد بنكراد (2016). - العمى الثقافي من هيمنة المؤسسة إلى شرعنة الأقلية / هاني اليونس (2019).